The production of hate crime victim status: Discourses of normalisation and the experiences of LGBT community members - Haynes, Amanda (Criminology & criminal justice, 2025)
This article identifies discourses which serve to ‘normalise’ experiences of anti-LGBT (Lesbian, Gay, Bisexual and Transgender) violence and prevent harmed LGBT persons from accessing the status of ‘hate crime victim’. The phenomenon of normalisation is established in research addressing homophobic, biphobic and transphobic violence, where it is understood fundamentally as the rendering unremarkable of violent manifestations of hate due to their ubiquity. This article interrogates the dynamics of the normalisation process. Drawing on a Foucauldian approach, we explore normalisation as a disciplinary practice, through which people who have experienced anti-LGBT violence are denied access to the status of hate crime victim. Through discourse analysis of focus group data, we identify obstacles to identification and self-identification as a victim grounded in the experience and anticipation of judgement both within society and the LGBT community. Discourses against which the claims of LGBT people are adjudicated (re)produce cultural myths about hate crime, about anti-LGBT violence and about victimhood. While this article acknowledges that the value of identifying as a victim is not uncontested, it also asserts that the practice of normalisation, in denying this status, impacts on access to justice and to support. Far from passive, LGBT people who do not self-identify as victims find ways to manage the impacts of hate using their own resources. In this manner, the disciplinary practice of ‘normalisation’ responsibilises persons harmed by social ills for their own care and silences potentially disruptive claims of victimhood on the part of marginal people.